Yield and nutritional quality of highbush blueberry genotypes trialled in a Mediterranean hot summer climate. (25th April 2020) - Mazzoni, Luca; Balducci, Francesca; Di Vittori, Lucia; Scalzo, Jessica; Capocasa, Franco; Zhong, Chuan‐Fei; Forbes‐Hernandez, Tamara Y; Giampieri, Francesca; Battino, Maurizio; Mezzetti, Bruno
Abstract: BACKGROUND: Cultivation of highbush blueberry ( Vaccinium corymbosum L.) has been increasing in Europe in recent years, in particular due to the availability of new genotypes suitable for cultivation in many different environmental conditions. The aim of this study was to evaluate the resilience and nutritional quality of 11 highbush blueberry cultivars and two new selections (from the New Zealand Institute for Plant and Food Research Ltd breeding program) in Mediterranean hot summer climate conditions by measuring plant yield, seasonality, fruit sensorial traits, and phytochemical content in the fruits. RESULTS: The new blueberry genotype PFR005 showed a high level of adaptability to these environmental conditions, with the highest total plant yield, whereas PFR075 was the best genotype for nutritional characteristics. Among the cultivars, 'Cosmopolitan' showed the maximum average fruit weight, 'Blueray' and 'Hortblue Poppins' demonstrated a good sensorial profile, while the best cultivars from the nutritional point of view were 'Hortblue Poppins', 'Hortblue Petite', and 'Early Blue'. Conclusion: New cultivars and new genotypes able to satisfy the needs of different users, have been identified. The integration of germplasm evaluation with a tailored breeding program will help to create new cultivars that will be useful for the expansion of blueberry cultivation in hot Mediterranean summer climate conditions, which up to now have limited this crop. © 2020 Society of Chemical Industry